2022
DOI: 10.3390/ijms232012492
|View full text |Cite
|
Sign up to set email alerts
|

Intact Type I Interferon Receptor Signaling Prevents Hepatocellular Necrosis but Not Encephalitis in a Dose-Dependent Manner in Rift Valley Fever Virus Infected Mice

Abstract: Rift Valley fever (RVF) is a zoonotic and emerging disease, caused by the RVF virus (RVFV). In ruminants, it leads to “abortion storms” and enhanced mortality rates in young animals, whereas in humans it can cause symptoms like severe hemorrhagic fever or encephalitis. The role of the innate and adaptive immune response in disease initiation and progression is still poorly defined. The present study used the attenuated RVFV strain clone 13 to investigate viral spread, tissue tropism, and histopathological lesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…Previous studies of RVFV have shown that type I interferon (IFN) responses are important in controlling infection peripherally [ 34 36 ]. However, it has not been tested if IFNs are protective in the brain, as IFN-treated neurons remain susceptible to some viral infections [ 25 , 26 , 28 , 30 , 37 ]. We tested this in vitro using the biosafety level two strain RVFV MP-12, which is attenuated by nine amino acid substitutions across all three genomic segments [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies of RVFV have shown that type I interferon (IFN) responses are important in controlling infection peripherally [ 34 36 ]. However, it has not been tested if IFNs are protective in the brain, as IFN-treated neurons remain susceptible to some viral infections [ 25 , 26 , 28 , 30 , 37 ]. We tested this in vitro using the biosafety level two strain RVFV MP-12, which is attenuated by nine amino acid substitutions across all three genomic segments [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Animal models are very useful for the study of viral infections; in particular, mice have become a powerful tool for RVFV research focused on the development of effective control measures such as vaccines and antivirals as well as for studies of viral pathogenesis [39][40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…This might be the reason why a robust T cell response induced by hRVFV-4s immunization did not translate into protective efficacy. A slow progressing RVFV encephalitis model [ 30 ] might be more suitable for testing the protective efficacy of virus-specific T cells induced by hRVFV-4s vaccination. Nevertheless, the efficiency with which VN antibodies induced after hRVFV-4s vaccination protected mice from developing severe hepatic disease promotes the assessment of VN titres in future clinical trials.…”
Section: Discussionmentioning
confidence: 99%